Implementasi Pembelajaran Technological Pedagogical Content Knowledge Untuk Meningkatkan Hasil Belajar Mata Pelajaran IPS Kelas IV SD - Qodri Jamalulail; Siti Rochmiyati (Universitas Sarjanawiyata Tamansiswa, 2023)
The purpose of this study is to describe the implementation and learning of TPACK (Technological Pedagogical Content Knowledge) to improve the learning outcomes of grade IV elementary school IPS subjects. This research method uses qualitative disripive research methods. TPACK stands for Technological Pedagogical and Content Knowledge. In Indonesian can be interpreted as knowledge of technology, pedagogy, and content. TPACK is a framework for education researchers and practitioners, in an effort to package and develop learning models to achieve learning goals through a better process. TPACK learning is one of the strategies that can be implemented with IPS learning in elementary school to improve learning outcomes. With TPACK-based IPS learning will provide meaningful IPS learning that has an impact on learning outcomes and a conducive learning climate. The hope is that through the Implementation of TPACK Learning (Technological Pedagogical Content Knowledge) can improve the learning outcomes of IPS Class IV elementary school subjects